Analisis Pengaturan dan Implementasi Pemilihan Kolom Kosong: Tinjauan Terhadap PKPU dan Undang-Undang Pemilihan Kepala Daerah - Larasati, Septifa Indah; Samhudi, Gamalel Rifqi (Universitas Muhammadiyah Kotabumi, 2024)
This study examines the regulation and implementation of empty-column voting in the context of regional head elections (pilkada), focusing on relevant regulations such as the KPU Regulations (PKPU) and the Pilkada Law. Regional head elections are a democratic process organized by the state to realize the people's sovereignty, as mandated in Article 1 paragraph (2) of the 1945 Constitution of the Republic of Indonesia. Over time, Pilkada in Indonesia has changed, especially with the enactment of the Pilkada Law. These changes gave rise to a new phenomenon in the Indonesian political system, namely the existence of a single candidate pair in the elections. Empty-column voting is a new concept in Indonesia's electoral system that allows voters to express their dissatisfaction with existing candidates by choosing an empty column as an alternative. This can be seen in the 2024 Simultaneous Regional Elections, where the elections in Banyumas Regency were conducted by a single candidate, which is a specific form of popular participation.